2012
DOI: 10.1098/rspb.2012.0397
|View full text |Cite
|
Sign up to set email alerts
|

Island phytophagy: explaining the remarkable diversity of plant-feeding insects

Abstract: Plant-feeding insects have undergone unparalleled diversification among different plant taxa, yet explanations for variation in their diversity lack a quantitative, predictive framework. Island biogeographic theory has been applied to spatially discrete habitats but not to habitats, such as host plants, separated by genetic distance. We show that relationships between the diversity of gall-inducing flies and their host plants meet several fundamental predictions from island biogeographic theory. First, plant-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 43 publications
2
23
0
Order By: Relevance
“…Higher dominance is associated with more host–consumer encounters (random placement hypothesis) and more ecological niches for consumers (habitat diversity hypothesis) (Miller, 2012; Strona & Fattorini, 2014). For example, the occurrence of more species in a plant family implies the existence of a greater number of available niches (de Araújo, dos Santos, & Gomes‐Klein, 2012; de Araújo, Silva, dos Santos, & Gomes‐klein, 2013; Joy & Crespi, 2012; Mendonça, 2007). Therefore, according to the plant family size hypothesis, larger plant families are expected to host more parasites (de Araújo, 2011; de Araújo et al., 2012, 2013; Cuevas‐Reyes, Quesada, Hanson, & Oyama, 2007; Dai et al., 2017; Fernandes, 1992; Gonçalves‐Alvim, Fernandes, & Goncalves‐Alvim, 2001; Lawton & Price, 1979; Mendonça, 2007; Price, 1977; Veldtman & McGeoch, 2003; Ward & Spalding, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Higher dominance is associated with more host–consumer encounters (random placement hypothesis) and more ecological niches for consumers (habitat diversity hypothesis) (Miller, 2012; Strona & Fattorini, 2014). For example, the occurrence of more species in a plant family implies the existence of a greater number of available niches (de Araújo, dos Santos, & Gomes‐Klein, 2012; de Araújo, Silva, dos Santos, & Gomes‐klein, 2013; Joy & Crespi, 2012; Mendonça, 2007). Therefore, according to the plant family size hypothesis, larger plant families are expected to host more parasites (de Araújo, 2011; de Araújo et al., 2012, 2013; Cuevas‐Reyes, Quesada, Hanson, & Oyama, 2007; Dai et al., 2017; Fernandes, 1992; Gonçalves‐Alvim, Fernandes, & Goncalves‐Alvim, 2001; Lawton & Price, 1979; Mendonça, 2007; Price, 1977; Veldtman & McGeoch, 2003; Ward & Spalding, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The variation in leafminer species richness among different host plants might be described by the species–area (i.e., leafminer species to host plant area) or species–apparency (i.e., leafminer species to host plant apparency) relationship (Dai et al., 2017; MacArthur & Wilson, 1967; Opler, 1974). “Area” here is a function of the distribution area, body size, number of individuals, and other indicators of plant dominance (Chaij, Devoto, Oleiro, Chaneton, & Mazía, 2016; Feeny, 1976; Joy & Crespi, 2012; Kamiya, O'Dwyer, Nakagawa, & Poulin, 2014; Miller, 2012). However, the unapparent relatives of apparent hosts might be utilized by leafminers due to the chemical similarities among phylogenetically closed plants (Dai et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Host-plant preferences are well characterized for gall midge species in 351 genera [41,43] which also may be categorized by the presence or the absence of fungal symbionts [15,30,43]. Both molecular and morphological analyses have also revealed that a small proportion (53 of the approx.…”
Section: Introductionmentioning
confidence: 99%
“…As with other phytophagous insects [38][39][40], gall midge host-plant shifts occur most often between closely related plants relative to distantly related plants, because shifts among distantly related plants require substantially more adaptation [6,39]. Thus, gall midges are constrained in the range of possible host-plant shifts by the genetic distance between plant taxa [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Further, the frequent shifts between evolutionarily distinct hosts observed in parasites have led to the analogy of considering plant species as resource islands separated by evolutionary distances (16)(17)(18). In this metaphor, related plants constitute resource archipelagos within which colonization of new resource islands entails few costs.…”
mentioning
confidence: 99%